Applied business tools and technology in tourism
"Technology plays a very important role in making tourism flourish. Technology has helped to replace costly human labor with technical labor in the tourism and hospitality industries. It helps minimize labor costs but also helps to prevent issues with customer service. The rapid development of digital technologies has impacted the tourism and hospitality industry as well. The means of spreading the information has changed, as well as the planning process, tourism product and services. In addition to making the travel product more diverse and easily accessible, all aspects of travel panning have also been accelerated. The digital transformation has created great opportunities for tourism businesses and destinations and has allowed them to increase their visibility on a larger market. However, on the other hand, competition has been increased as well and it has caused many challenges for small and medium enterprises. The tourism industry itself is a great source of information and at the same time consumes a huge amount of data. Consequently, digital technologies play a huge role in the daily affairs of tourism and cover almost all of its stages - communication with customers, planning, booking, business management, etc. The text is thoroughly revised and new chapters are added in this edition that examines the transformation of the tourism as a result of the Information Technology (IT) revolution. It explains that students need to be much more familiar with technological aspects, as it already determines the competitiveness of organizations. The book explains the gaps between the tourism business and ICT influence and suggests measures to fill the gaps in tourism enterprises. Strategically, the aim of the book is to integrate ICT with tourism that will enable more accessibility, visibility of information, availability of variety of products and satisfaction."--